New acylides: synthesis of 3-O-[γ-(4-oxo-2-aryl-thiazolidin-3-yl)butyryl]erythromycin A derivatives - Deepa Pandey (Beilstein Journal of Organic Chemistry, 2008)
In search of new erythromycin derivatives 3-O-[γ-(4-oxo-2-aryl-thiazolidin-3-yl)butyryl]erythromycin A derivatives have been synthesized. The 3-hydroxy group was derivatised to a primary amine and subsequently the thiazolidinone nucleus was generated at the amino functionality through DCC mediated one-pot three-component reaction in good yields.